Diagnostic value of T2 relaxation time for hepatic iron grading in rat model of fatty and fibrotic liver - Mingli Jin; Yin Jiang; Qi Zhao; Zhihua Pan; Fang Xiao (PLoS ONE, 2022)
The objective of this study was to assess the quantitative diagnostic value of T2 relaxation time for determining liver iron grades in the presence of fat and fibrosis. Sixty Sprague-Dawley (SD) male rats were randomly divided into control (10 rats) and model (50 rats) groups. The model group of coexisting iron, steatosis, and liver fibrosis was induced by intraperitoneal injection of carbon tetrachloride (CCl4) dissolved in edible vegetable oil (40% v/v). The control group received an intraperitoneal injection of 0.9% saline. All rats underwent multi-echo gradient and spin echo (M-GRASE) magnetic resonance imaging, and the T2 relaxation time of the liver was measured. The rats were killed immediately after imaging, and liver specimens were extracted for histological evaluation of steatosis, iron, and fibrosis. The relationship and differences between T2 relaxation time and liver fibrosis stage, as well as the pathological grade of hepatic steatosis, were assessed by Spearman’s rank correlation coefficient, non-parametric Mann–Whitney test, and the Kruskal–Wallis test. The area under the receiver operating characteristic curve and interaction analysis were used to quantify the diagnostic performance of T2 relaxation time for detecting different degrees of liver iron grades. Six normal control rats and 34 model rats were included in this study. Fibrosis stages were F0 (n = 6), F1 (n = 6), F2 (n = 8), F3 (n = 10), and F4 (n = 10). Steatosis grades were S0 (n = 5), S1 (n = 8), S2 (n = 12), and S3 (n = 15). Hepatocyte or Kupffer cell iron grades were 0 (n = 7), 1 (n = 9), 2 (n = 12), 3 (n = 10), and 4 (n = 2). The liver fibrosis stages were positively correlated with the iron grades (P < 0.01), and the iron grades and fibrosis stages were negatively correlated with the T2 relaxation time (P < 0.01). The T2 relaxation times exhibited strongly significant differences among rats with different histologically determined iron grades (P < 0.01). Pairwise comparisons between each grade of liver iron indicated significant differences between all iron grades, except between grades 0 and 1, and between grades 1 and 2 (P > 0.05). The T2 relaxation time of the liver had an area under the receiving operating characteristic curve (AUC) of 0.965 (95% CI 0.908–0.100, P < 0.001) for distinguishing rats with a pathological grade of hepatic iron (grade ≥ 1) from those without, an AUC of 0.871 (95% CI 0.757–0.985, P < 0.001) for distinguishing rats with no iron overload (grade ≤ 1) from rats with moderate or severe iron overload (grade ≥ 2), and an AUC of 0.939 (95% CI 0.865–1.000, P < 0.001) for distinguishing rats with no to moderate iron overload (grade ≤ 2) from rats with severe iron overload (grade 3). The interaction of different pathological grades of iron, steatosis, and fibrosis has a negligible influence on the T2 relaxation time (P > 0.05). In conclusion, T2 relaxation time can assess histologically determined liver iron grades, regardless of coexisting liver steatosis or fibrosis; therefore, it is suitable for distinguishing between the presence and absence of iron deposition and it is more accurate for higher iron grading.